Creative process and creative environment: impact on experience quality and behavioural intentions in creative tourism services - Mohd Fahmi Yahaya; Ahmad Azmi M. Ariffin (Creativity Studies)
This research investigates the intricate relationships between creativity process and environment, experience quality, and behavioural intentions within the unique context of creative tourism service providers. Sustainable issues related to cultural tourism especially in relation to the preservation and conservation of national heritage has fuelled the need to rebrand some tourists’ hotspots in Malaysia as a creative destination. However, service providers in this domain struggles to retain their customers, necessitating the exploration of effective marketing strategies based on their creative resources. Drawing from a comprehensive dataset of 500 respondents, obtained through purposive sampling, this study investigates the interplay among these factors and their ultimate impact on tourist’s intentions in the creative tourism industry. Employing partial least squares structural equation modelling, the study reveals that creativity, manifested through creative behaviour and innovative ideas, significantly influences the experience quality offered to tourists. Furthermore, this study underscores the essential role of physical and social environments in nurturing creativity and shaping experience quality. Experience quality emerges as a critical mediator in this intricate web of relationships, bridging the gap between creativity and behavioural intentions. The findings offer guidance to creative tourism service providers in enhancing their offerings, optimising physical and social environments, and elevating the experience quality they deliver. These insights are expected to not only benefit the industry but also contribute to a broader understanding of the intricate interplay between creativity, experience quality, and behavioural intentions in the realm of creative tourism.